ABCB transporters in a leaf beetle respond to sequestered plant toxins. Issue 1934 (2nd September 2020) - Kowalski, Paulina; Baum, Michael; Körten, Marcel; Donath, Alexander; Dobler, Susanne
Abstract : Phytophagous insects can tolerate and detoxify toxic compounds present in their host plants and have evolved intricate adaptations to this end. Some insects even sequester the toxins for their defence. This necessitates specific mechanisms, especially carrier proteins that regulate uptake and transport to specific storage sites or protect sensitive tissues from noxious compounds. We identified three ATP-binding cassette subfamily B (ABCB) transporters from the transcriptome of the cardenolide-sequestering leaf beetle Chrysochus auratus and analysed their functional role in the sequestration process. These were heterologously expressed and tested for their ability to interact with various potential substrates: verapamil (standard ABCB substrate), the cardenolides digoxin (commonly used), cymarin (present in the species's host plant) and calotropin (present in the ancestral host plants). Verapamil stimulated all three ABCBs and each was activated by at least one cardenolide, however, they differed as to which they were activated by. While the expression of the most versatile transporter fits with a protective role in the blood–brain barrier, the one specific for cymarin shows an extreme abundance in the elytra, coinciding with the location of the defensive glands. Our data thus suggest a key role of ABCBs in the transport network needed for cardenolide sequestration.